Assessment of upper GI motor activity and GI symptoms in patients with amyotrophic lateral sclerosis: an observational study - Ribichini, Emanuela; Pallotta, Nadia; Badiali, Danilo; Carlucci, Maria; Ceccanti, Marco; Cambieri, Chiara; Libonati, Laura; Corazziari, Enrico Stefano; Ruoppolo, Giovanni; Inghilleri, Maurizio (Frontiers in Neurology, 2025)
Background/aimsOro-pharyngeal dysfunction has been reported in Amyotrophic Lateral Sclerosis (ALS). We aimed to assess ALS patients upper gastrointestinal (GI) motor activity and GI symptoms according to bulbar and spinal onset and severity of ALS.MethodsALS bulbar (B) and spinal (S) patients with ALS Functional Rating Scale (ALSFRS-r) ≥35, bulbar sub-score ≥10, and Forced Vital Capacity (FVC) >50%, underwent to: Fiberoptic Endoscopic Evaluation of Swallowing (FEES); esophageal manometry; gastric emptying; Rome symptom questionnaire. Medical Research Council Scale for Muscle Strength (MRC) was performed for the upper and lower limbs. Mann-Whitney's U, Fisher's ranks test, Pearson's test was used.ResultsThirteen ALS patients were included (6 F; mean age 61.2 ± 13.7 years, range: 37-87), 5 with B and 8 with S onset (ALSFRS-R score 39.5 ± 4.9, MRC score 128.6 ± 23.3, disease duration 22.8 ± 17.9 months). FEES detected a high dysphagia score in 5 patients with no difference between S and B phenotype. Lower esophageal sphincter pressure was normal in all patients. Esophageal dysmotility was observed in three S and two B onset patients. Upper esophageal sphincter (UES) pressure was higher in all ALS patients. UES spasms and delayed gastric emptying were detected in two B and one S and in two B and four S patients, respectively. There was no correlation between esophagogastric motor abnormalities and clinical characteristics of ALS, nor GI symptoms.ConclusionsThe presence of UES spasm and the delayed gastric emptying in a subgroup of ALS patients may suggest the role of ANS dysfunction in ALS.